2014
DOI: 10.1128/genomea.01013-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome of Chilean Honeybee (Apis mellifera) Gut Strain Lactobacillus kunkeei MP2

Abstract: Here, we report the first draft genome sequence of Lactobacillus kunkeei strain MP2, isolated from a Chilean honeybee gut. The sequenced genome has a total size of 1.58 Mb distributed into 44 contigs and 1,356 protein-coding sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 11 publications
0
15
2
Order By: Relevance
“…The L. kunkeei strain MP2 reported in this study was isolated in a previous study from the gut of a honey bee (Apis mellifera), collected from commune hives in the Maria Pinto area, Melipilla Province in the Central zone of Chile (Olmos et al, 2014).…”
Section: Dna Isolation and Genome Sequencingmentioning
confidence: 86%
See 4 more Smart Citations
“…The L. kunkeei strain MP2 reported in this study was isolated in a previous study from the gut of a honey bee (Apis mellifera), collected from commune hives in the Maria Pinto area, Melipilla Province in the Central zone of Chile (Olmos et al, 2014).…”
Section: Dna Isolation and Genome Sequencingmentioning
confidence: 86%
“…A comparison of the assembly of L. kunkeei MP2 obtained in this work, with the previously obtained using Illumina sequencing (Olmos et al, 2014), is shown on Figure 1. All of the previous assembled contigs mapped to the current assembly, and several gaps on the sequence were completed in this new version of the genome.…”
Section: Assembly Descriptionmentioning
confidence: 94%
See 3 more Smart Citations